Residence-based Capital Taxation: Why Information is Voluntarily Exchanged and why it is not - Wolfgang Eggert; Martin Kolmar (Center for Economic Studies and ifo Institute (CESifo), 2000)
The issue of capital tax competition in source-based capital taxes is viewed to be unproblematic if residence-based capital taxation exists. The sustainability, however, of residence-based capital taxation depends on the co-operation of source countries to assist in collecting tax revenues that benefit the residence country. We analyze conditions under which information about foreign savings are voluntarily exchanged. It turns out that information is voulntarily exchanged if the wage structure of the economy is not influenced by the size of the financial sector resulting in an efficient allocation with decentralized tax policies. In contrast, strategic incentives to withhold information may exist if the size of the financial sector has a positive impact on the wage structure of an economy.
Keywords: 330; Tax competition; information exchange